Appendiceal Enterobius Vermicularis infestation discovered incidentally in a case of sigmoid volvulus: A Rare Co-occurrence - Archana Shetty; Nidha Gaffoor; Aparna Muralidhar (Tropical Journal of Pathology and Microbiology, 2022)
Enterobius Vermicularis is a gastrointestinal parasite mainly affecting children. It is one of the manycauses of acute appendicitis. The probability that every case of infestation leads to an appendicealinflammatory response is controversial, as cases with normal histology have been reported.Appendix is subjected to examination only when the patient presents, with symptoms primarilyrelated to it or attributed to obstructive causes of acute abdomen like intussusception, mass lesions,strictures or volvulus. The case presented is an adult who was operated for sigmoid volvulus withincidental finding of Enterobius Vermicularis infestation in the appendix. Though incidental,identification of worms is important as antihelminthic therapy can be curative, avoiding unduesurgical interventions